Strength Improvements of Different 10-Week Multicomponent Exercise Programs in Elderly Women - González-Ravé, José María; Cuéllar-Cañadilla, Rubén; García-Pastor, Teresa; Juárez Santos-García, Daniel (Frontiers in Public Health, 2020)
The purpose of this study was to analyze and compare the effects of various muscle strength sessions performed during 10 weeks physical conditioning programs and 4 weeks of detraining on the physical conditioning, body composition and hematology of elderly women. 48 women were randomly distributed in four groups: a physical conditioning group (PCG; n = 12) with two sessions per week; a PCG with an extra-session focus on hypertrophy (PCGH; n = 12), a PCG with an extra-session in a shallow pool (PCGP; n = 12); and a control group (CG; n = 12). PCGH achieved a significant increase in Abalakov. Significant differences between the CG and the other groups were found in Countermovement Jump. There were significant improvements in the chair-stand test in the PCG and PCGH. The training programs suspected improvements in HDL, LDL, baseline glucose and glycated hemoglobin. In conclusion, a training program with an extra-session focus on hypertrophy achieved a greater improvement in strength in elderly women.